2016
DOI: 10.1097/rlu.0000000000000872
|View full text |Cite
|
Sign up to set email alerts
|

SPECT Myocardial Blood Flow Quantitation Concludes Equivocal Myocardial Perfusion SPECT Studies to Increase Diagnostic Benefits

Abstract: Recently, myocardial blood flow quantitation with dynamic SPECT/CT has been reported to enhance the detection of coronary artery disease in human. This advance has created important clinical applications to coronary artery disease diagnosis and management for areas where myocardial perfusion PET tracers are not available. We present 2 clinical cases that undergone a combined test of 1-day rest/dipyridamole-stress dynamic SPECT and ECG-gated myocardial perfusion SPECT scans using an integrated imaging protocol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 7 publications
1
0
0
Order By: Relevance
“…Nevertheless, cardiac PET imaging has limitations due to high cost and sometimes low cyclotron availability. Hsu et al reported the use of dynamic SPECT/CT to measure absolute MBF to enhance CAD detection and diagnosis [2,4]. According to this case, we found that dynamic SPECT/CT could provide much earlier information in terms of flow parameters to rescue the jeopardized myocardium in post-PCI evaluation.…”
supporting
confidence: 51%
“…Nevertheless, cardiac PET imaging has limitations due to high cost and sometimes low cyclotron availability. Hsu et al reported the use of dynamic SPECT/CT to measure absolute MBF to enhance CAD detection and diagnosis [2,4]. According to this case, we found that dynamic SPECT/CT could provide much earlier information in terms of flow parameters to rescue the jeopardized myocardium in post-PCI evaluation.…”
supporting
confidence: 51%